(untitled) (Journal of Ideas in Health, 2024)
Background: Zoonotic diseases are the major public health threat, with over 70% originating from wildlife. Rodents, while beneficial to the environment, transmit many zoonotic diseases such as hemorrhagic fevers, plague, tularemia, and leptospirosis, mainly due to increased agriculture and land use changes. Understanding rodent-borne pathogens is essential for effective intervention. Therefore, this study aimed to identify pathogenic and zoonotic bacteria in rodents and identify rodent species in the study area. Methods: A total of 116 rodents achieved samples (101 oral-pharyngeal and 15 rectal swabs) collected from Kibondo, Uvinza and Kyerwa were used in this study. Total RNA (Ribonucleic Acid) was extracted from each swab sample and then pooled based on rodent species, location and swab types to make twelve pools. A portion of pooled swabs were polyadenylated and used for metagenomics sequence libraries preparation. A 16S rRNA (ribosomal Ribonucleic Acid) metagenomics sequencing was performed on 12 pools by using MinIon platform in order to identify microbial diversity. Results: A total of 13 different microbial communities includinng bacteria were identified; where, 15 families of potentially pathogenic, zoonotic and bacteria of unknown zoonotic potential were also identified. These families included Mycobacteriacea, Helicobacteriacea, Enterobacteriacea, Vibrionacea, Staphylococcaceae, Nocardiaceae, Bacillaceae, Pasteurellaceae, Streptococcaceae, Campylobacteraceae, Leptospiraceae, Brachyspiraceae, Moraxellaceae, Enterococcaea, Flavobacteriacea. Potentially zoonotic pathogenic bacteria including Mycobacterium tuberculosis, Vibrio cholerae, Helicobacter pylori and Vibrio parahaemolyticus are reported in this study. Conclusion: This study identifies several bacteria of public and veterinary importance, highlighting the possibility of increased risk of human infection and risk of cross-transmission between rodents, humans, and animals given the proximity between rodents, humans and animals. While no concrete evidence of rodent-to-human transmission was found, we hypothesize that rodents are a potential infection source, especially in resource-poor areas with close rodent-human contact.